Finite element analysis of left ventricle motion and mechanical properties in three dimensions / Abdallah Ibrahim Mohammed Hasaballa - Abdallah Ibrahim, Mohammed Hasaballa (2013)
Despite the wide variety of research in medicine and bioengineering treatment strategies developed over the last half century, heart disease remains among the most serious diseases threatening human longevity. Modeling the mechanics of the human myocardium, particularly the left ventricle, which is the main pumping chamber and most common site for heart disease, plays a significant role in better understanding the performance of the heart in healthy and diseased states. The core part of this work constitutes the implementation of a more realistic three-dimensional finite element model of the human left ventricle to provide a reliable description of both myofiber orientation and material characteristics. In this study, direct and inverse finite element methods of human left ventricle were developed. The direct finite element method is suitable for studying the influences of different mesh densities, constitutive models, fibers orientations, and myofiber volume fractions. Meanwhile, the inverse finite element method served to determine the bulk modulus of the left human ventricle during a cardiac cycle. The simulation results indicate that the changes in transverse angle hardly affected the pressure-volume relation of the ventricle, but significantly do so with changes in helix angle (up to 50% change). The ejection fraction decreased with decreasing total volume fraction (increasing the infarct myocardial volume). Total volume fraction of less than 60% deceased the ejection fraction by over 50%. Thus, the myofibers’ architecture plays a significant role in the mechanics of the left ventricle. Finally, the myocardium bulk modulus may be employed as a diagnostic tool (clinical indicator) for heart ejection fraction, and hence, heart function performance. Therefore, this study offers a new perspective and means of studying living-myocardium tissue properties. The research may also pave the way towards more effective treatment.